Dispatching from Depot Repair in a Recoverable Item Inventory System: On the Optimality of a Heuristic Rule - Miller, Bruce L. (Management Science, 1974)
This paper examines real-time decision rules for a U.S. Air Force inventory system where items are repaired rather than “used up.” The problem is to decide which user in the system has the greatest need for the newly available inventory items coming out of repair. The system is modeled as a Markov decision process and a heuristic rule is presented. This rule, the Transportation Time Look Ahead policy, is justified theoretically by showing that the rule is optimal for a modified model. Thus we have a theoretical justification of a decision rule in a large scale dynamic programming application.